Antiviral Immune Response in Alzheimer’s Disease: Connecting the Dots - Roy, Ethan R.; Cao, Wei (Frontiers in Neuroscience, 2020)
Alzheimer’s disease (AD) represents an enormous public health challenge currently and with increasing urgency in the coming decades. Our understanding of the etiology and pathogenesis of AD is rather incomplete, which is manifested in stagnated therapeutic developments. Apart from the well-established Amyloid Hypothesis of AD, gaining traction in recent years is the Pathogen Hypothesis, which postulates a causal role of infectious agents in the development of AD. Particularly, infection by viruses, among a diverse range of microorganisms, has been implicated. Recently, we described a prominent antiviral immune response in human AD brains as well as murine amyloid beta models, which has consequential effects on neuropathology. Such findings expectedly allude to the question about viral infections and AD. In this Perspective, we would like to discuss the molecular mechanism underlying the antiviral immune response, highlight how such pathway directly promotes AD pathogenesis, and depict a multilayered connection between antiviral immune response and other agents and factors relevant to AD. By tying together these threads of evidence, we provide a cohesive perspective on the uprising of antiviral immune response in AD.